High-temperature piezoelectric sensing element and preparation method thereof
By using (Na2+Nb2/5)xTi(1-x)O3 ceramic powder and trace SiO2 and Fe2O3 in piezoelectric materials, combined with lead-free formula and detailed preparation process, environmental pollution of piezoelectric materials during sintering is solved. and the problem of unstable structure, the preparation of high-density ceramic bodies and excellent piezoelectric properties are achieved, and are suitable for high-temperature harsh environments.
Patent Information
- Application Number
- CN202411303580.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-13
AI Technical Summary
Existing piezoelectric materials are prone to environmental pollution during sintering, and their structure is unstable, making it difficult to maintain performance in high temperature and harsh environments.
(Na2+Nb2/5)xTi(1-x)O3 is used as ceramic powder material, and the x, a and b parameters in the chemical formula are adjusted by adding trace amounts of SiO2 and Fe2O3 to prepare a high-density ceramic body. Lead-free formula combines multiple drying, filtration, pre-firing, sintering and other steps to remove impurities and moisture, ensuring the purity and mechanical strength of the product.
It realizes the preparation of high-density ceramic bodies, excellent piezoelectric properties, can maintain stability in high-temperature and high humidity environments, reduces environmental pollution, and is suitable for high-temperature harsh environments such as automobile engines and gas turbines, ensuring long-term use of products and High quality output.
Smart Images

Figure CN119118655A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-temperature piezoelectric sensor elements, and in particular relates to a high-temperature piezoelectric sensor element and a preparation method thereof. Background Art
[0002] High-temperature piezoelectric sensing elements have thermoelectric and piezoelectric functions, can be used for thermal energy collection and vibration energy collection, and have thermoelectric conversion and electromechanical conversion functions. They can also be designed and made into thermal or mechanical vibration sensors. Therefore, in high-temperature and harsh environments such as automobile engines, gas turbines, boilers, oil extraction and pipeline transportation, they can not only collect energy but also monitor the operating status of equipment through thermoelectric and electromechanical signals.
[0003] The existing patent CN109320244B discloses a low-temperature sintered piezoelectric ceramic material and its preparation method. Its general chemical formula is xPby(Yb1 / 2Nb1 / 2)O2+y-(1-x)PbyTiO2+y+u%LiSbO3+v%MaOb. However, lead is a heavy metal and the structure of the piezoelectric material is unstable during the sintering process. Lead is very easy to volatilize and cause environmental pollution.
[0004] Therefore, in order to solve the above problems, it is necessary to design a high-temperature piezoelectric sensor element and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a high-temperature piezoelectric sensor element and a preparation method thereof, so as to solve the technical problem that the existing piezoelectric materials are prone to cause environmental pollution during preparation.
[0006] In order to solve the above technical problems, the present invention provides a high-temperature piezoelectric sensor element, the general chemical formula of which is: (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3; in the formula (Na2+Nb 2 / 5 )xTi(1-x)O3 represents the basic ceramic powder material, aWt% represents the weight percentage of SiO2 in the ceramic powder, and bWt% represents the weight percentage of Fe2O3 in the ceramic powder; wherein (Na2+Nb 2 / 5 ) and Ti have a molar ratio of x:(1-x); a<0.1, b<0.5; and 0.25<x<0.35.
[0007] On the other hand, the present invention also provides a method for preparing a high-temperature piezoelectric sensor element, comprising: S1, raw material pretreatment: put each chemical raw material into an oven at a constant temperature of 120℃~160℃ and dry it for 10~14h, then cool it to room temperature and take out the ingredients to be mixed; S2, ingredients; the dried sodium carbonate, titanium oxide, niobium pentoxide, silicon oxide, and iron oxide are mixed in a molar ratio of 36.7:45:18.3:0.05:0.2; S3, powder preparation: mixing the proportioned materials and crushing them to the required particle size; S4, preforming of the original part; adding the raw material powder into the mixed solvent, mixing, casting and punching into the required shape; S5, firing; removing the binder solid and a small amount of solvent components in the ceramic green sheet and sintering; S6, upper electrode; firing the ceramic sheet brushed with silver paste, and placing the fired ceramic sheet in a DC voltage to generate polarization intensity; S7, finished product testing; testing various parameters of the product.
[0008] The beneficial effects of the present invention are: (I) The present invention adopts (Na2+Nb 2 / 5 )xTi(1-x)O3 is a ceramic powder material that conforms to the ABO3 perovskite structure. By adding trace amounts of SiO2 and Fe2O3, a high-density ceramic body is obtained, and excellent piezoelectric properties are achieved. At the same time, by adjusting parameters such as x, a, b in the chemical formula, the performance of the sensor element can be customized to meet the specific needs of different application scenarios. At the same time, the present invention also adopts a lead-free formula, which reduces the use of heavy metals such as lead. While meeting the piezoelectric properties, it reduces pollution to the environment and solves the technical problem that existing piezoelectric materials are prone to causing environmental pollution during preparation.
[0009] (ii) The special ratio and material selection in the chemical formula of the present invention enable the sensor element to not only withstand a higher operating voltage, but also maintain stable performance in a high temperature and high humidity environment. The product will not fail after long-term use and is suitable for high temperature and harsh environments such as automobile engines, gas turbines, and boilers.
[0010] (III) The present invention removes impurities and moisture in the material through multiple drying, filter pressing, pre-calcining, sintering and other steps, thereby improving the purity and density of the product and ensuring the mechanical strength and durability of the product.
[0011] (IV) The present invention ensures that the sensing element has excellent piezoelectric properties and can accurately convert mechanical vibrations into electrical signals by precisely controlling the molar ratio and weight percentage of each component and optimizing the preparation process. At the same time, the preparation method is detailed and the steps are clear. From raw material pretreatment to finished product testing, each step is strictly controlled and optimized to ensure the quality and consistency of the product.
[0012] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description and the drawings.
[0013] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 It is a flow chart of a preferred embodiment of the preparation method of the present invention. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0017] This embodiment provides a high-temperature piezoelectric sensor element, the general chemical formula of which is: (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3; where (Na2+Nb 2 / 5 )xTi(1-x)O3 represents the basic ceramic powder material, aWt% represents the weight percentage of SiO2 in the ceramic powder, and bWt% represents the weight percentage of Fe2O3 in the ceramic powder; wherein (Na2+Nb 2 / 5 ) and Ti have a molar ratio of x:(1-x); a<0.1, b<0.5; and 0.25<x<0.35.
[0018] In this embodiment, by using (Na2+Nb 2 / 5)xTi(1-x)O3 is a ceramic powder material that conforms to the ABO3 perovskite structure. By adding trace amounts of SiO2 and Fe2O3, a high-density ceramic body is obtained, and excellent piezoelectric properties are achieved. At the same time, by adjusting parameters such as x, a, b in the chemical formula, the performance of the sensor element can be customized to meet the specific needs of different application scenarios. At the same time, the present invention also adopts a lead-free formula, which reduces the use of heavy metals such as lead. While meeting the piezoelectric properties, it reduces pollution to the environment and solves the technical problem that existing piezoelectric materials are prone to causing environmental pollution during preparation. Example 2
[0019] like Figure 1 As shown, this embodiment 2 provides a method for preparing the high-temperature piezoelectric sensor element, comprising: S1, raw material pretreatment: put each chemical raw material into an oven at a constant temperature of 120℃~160℃ and dry it for 10~14h, then cool it to room temperature and take out the ingredients to be mixed; S2, ingredients; the dried sodium carbonate, titanium oxide, niobium pentoxide, silicon oxide, and iron oxide are mixed in a molar ratio of 36.7:45:18.3:0.05:0.2; S3, powder preparation: mixing the proportioned materials and crushing them to the required particle size; S4, preforming of the original part; adding the raw material powder into the mixed solvent, mixing, casting and punching into the required shape; S5, firing; removing the binder solid and a small amount of solvent components in the ceramic green sheet and sintering; S6, upper electrode; firing the ceramic sheet brushed with silver paste, and placing the fired ceramic sheet in a DC voltage to generate polarization intensity; S7, finished product testing; testing various parameters of the product.
[0020] The step S3 further comprises: S31, mixing materials; fully stirring and mixing the mixed raw materials, ball milling medium and deionized water in a molar ratio of 1:2:0.6; S32, filter pressing; the mixed slurry is sealed and placed, and after standing, the air pressure valve is opened, and the pressure is 0.3-0.5MPa for filter pressing, and then closed after no water drips out; S33, drying; placing the filtered material in an oven at a constant temperature of 120°C to 160°C for drying to remove moisture from the surface of the material; S34, pre-firing; placing the material from which surface moisture has been removed into a pre-firing furnace for calcining to generate a porcelain material; wherein the pre-firing furnace has a heating rate of 4°C / min; and the maximum synthesis temperature is set at 1010°C to 1050°C and is kept at this temperature for 2.5 hours; S35, crushing: preliminarily crushing the pre-fired block porcelain material; S36, abrasive; the crushed porcelain material, ball milling medium and deionized water are fully stirred at a molar ratio of 1:2:0.6 to preliminarily grind the porcelain material, and then finely grind the preliminarily ground porcelain material to meet production requirements; S37, filter pressing; the ground porcelain powder slurry is sealed and placed, and after standing, the air pressure valve is opened, and the pressure is 0.3-0.5MPa for filter pressing, and then closed after no water drips out; S38, drying; placing the ceramic powder slurry after the filter press into an oven at a constant temperature of 120°C to 160°C for drying, and obtaining ceramic powder after the moisture of the material is completely removed.
[0021] In this embodiment, impurities and moisture in the material are removed through multiple drying, filter pressing, pre-calcining, sintering and other steps, thereby improving the purity and density of the product while ensuring the mechanical strength and durability of the product.
[0022] The S4 further comprises: S41, slurry preparation; mixing ceramic powder, ball milling medium, adhesive and anhydrous ethanol in a molar ratio of 7.5:15:1.425:2.6 and rolling for 20 to 30 hours to prepare a uniform ceramic slurry with a certain viscosity; S42, tape casting; pouring the ceramic slurry into the tape casting box in the tape casting machine, the slurry on the moving steel belt is scraped by the tape casting scraper into a slurry layer of a certain thickness, and the formed ceramic film belt is taken out after being dried in the drying oven of the tape casting machine; wherein the conveying speed of the steel belt is 1 to 1.4 cm / s; and the drying oven temperature is 40°C to 60°C.
[0023] S43, isostatic pressing; the stacked ceramic membrane strip is statically pressed into shape using an isostatic pressing device; S44, punching: punching the isostatically pressed ceramic film strip into green sheets of the required shape.
[0024] The S5 further comprises: S51, plastic removal; placing the green sheet into a plastic removal furnace for heating to remove the binder solid and a small amount of solvent components in the green sheet; wherein the plastic removal furnace has a heating rate of 0.3°C / min; and the maximum temperature of the plastic removal furnace is set to 600°C and kept at this temperature for 0.5h; S52, sintering; placing the green sheet after plastic removal into an electric furnace and sintering for 1.2 hours; wherein the sintering temperature is 1200°C to 1260°C.
[0025] The S6 further includes: S61, silver coating; printing the silver paste onto the ceramic sheet by a silk screen printing device; S62, silver burning; placing the silver-coated ceramic sheet into a silver burning electric furnace to burn and infiltrate the silver paste with the ceramic sheet to form an electrode; wherein the maximum silver burning temperature is 770°C and is kept warm for 0.2h; and the silver burning heating time is 1.8h.
[0026] S63, polarization; put the silver-sintered ceramic sheet into an oven polarization box, set the temperature to 100°C, and slowly pressurize to 6-7KV using a withstand voltage tester to generate polarization strength for the ceramic sheet.
[0027] In this embodiment, through the steps of silver coating, silver burning and polarization, a stable electrode is effectively formed on the ceramic sheet, thereby improving the conductivity and signal transmission efficiency of the sensor.
[0028] The S7 includes: S71, appearance inspection: inspecting product appearance and removing defective products.
[0029] In the embodiment of the present invention, according to the above preparation method, (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3 material performance at different x, a, b values Table 1; According to the above preparation method, (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3 material performance under the same x value and different a and b values Table 2; According to the above preparation method, (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3 material performance under the same a value and different x and b values Table 3; According to the above preparation method, (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3 material performance under the same b value and different x and a values is shown in Table 4; Note: The high temperature piezoelectric constant d33 line represents the piezoelectric constant of the material at 200°C, which is used to evaluate the stability of the piezoelectric performance of the material in a high temperature environment.
[0030] The high humidity dielectric constant εr row indicates the dielectric constant of the material in a high humidity environment with a relative humidity (RH) of 90%. It is used to evaluate the material's moisture resistance and electrical performance in a high humidity environment.
[0031] Combining the sample data provided in the table (samples 1 to 20), we can observe that (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3 material performance change trends at different x values, SiO2 content (a value) and Fe2O3 content (b value). The following is a detailed analysis of these trends: 1. The influence of x value 1. Changes in x value: x value represents the A-site ion (Na2+Nb 2 / 5) to the B-site ion (Ti), it can be seen from the sample group that the x value varies from 0.25 to 0.34.
[0032] 2. Density: As the x value increases, the density generally shows an increasing trend, but it is not a strictly linear relationship. This may be due to the increase in A-site ions leading to the densification of the crystal structure, but it may also be affected by other factors (such as the addition of SiO2 and Fe2O3).
[0033] 3. Piezoelectric constant: The piezoelectric constant (d33) at room temperature and high temperature is sensitive to changes in the x value. When the x value is moderate (such as 0.30-0.33), the piezoelectric constant is usually higher. However, too high x value (such as sample 4 and sample 5) may lead to a decrease in piezoelectric performance.
[0034] 4. Electromechanical coupling coefficient: The electromechanical coupling coefficient (kp) also changes with the change of x value, but the trend is not as obvious as the piezoelectric constant. Overall, a moderate x value helps to obtain a higher electromechanical coupling coefficient.
[0035] 5. Dielectric constant: The dielectric constant (εr) increases with the increase of x value, which may be because the increase of A-site ions changes the polarization characteristics and electrical properties of the material.
[0036] 2. Influence of SiO2 content (a value) 1. Changes in SiO2 content: SiO2 content ranges from 0.01wt% to 0.09wt%.
[0037] 2. Density: The addition of SiO2 usually increases the density of the material, but the effect is relatively small.
[0038] 3. Piezoelectric constant: The addition of SiO2 has a significant effect on the piezoelectric constant. An appropriate amount of SiO2 (such as about 0.05wt%) can improve the piezoelectric constant, but too much SiO2 (such as 0.09wt% in sample 5) may lead to a decrease in piezoelectric performance.
[0039] 4. Electromechanical coupling coefficient: The electromechanical coupling coefficient is also affected by the SiO2 content, but the trend is not as obvious as the piezoelectric constant.
[0040] 5. Dielectric constant: The addition of SiO2 will significantly increase the dielectric constant, especially the dielectric constant under high humidity conditions.
[0041] 3. Influence of Fe2O3 content (b value) 1. Changes in Fe2O3 content: Fe2O3 content ranges from 0.1wt% to 0.45wt%.
[0042] 2. Density: Fe2O3 has a relatively small effect on density, but in some cases (such as samples 2 and 5) it may lead to a decrease in density.
[0043] 3. Piezoelectric constant: The effect of Fe2O3 addition on the piezoelectric constant is more complicated. An appropriate amount of Fe2O3 (such as about 0.2wt%) may have a positive effect on the piezoelectric constant, but too much Fe2O3 (such as samples 4 and 5) will lead to a significant decrease in piezoelectric performance.
[0044] 4. Electromechanical coupling coefficient: The electromechanical coupling coefficient is also affected by the Fe2O3 content, but the overall trend is not as obvious as the piezoelectric constant.
[0045] 5. Dielectric constant: The addition of Fe2O3 will increase the dielectric constant, especially under high humidity conditions, however, too much Fe2O3 (such as samples 17-20) may cause the dielectric constant to grow slower or slightly decrease.
[0046] According to the above preparation method, (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3 material performance under different x, a, b value reverse range Table 5; According to the above preparation method, (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3 material performance under different x, a, b value reverse ranges Table 6; Note: The high temperature piezoelectric constant d33 line represents the piezoelectric constant of the material at 200°C, which is used to evaluate the stability of the piezoelectric performance of the material in a high temperature environment.
[0047] The high humidity dielectric constant εr row indicates the dielectric constant of the material in a high humidity environment with a relative humidity (RH) of 90%. It is used to evaluate the material's moisture resistance and electrical performance in a high humidity environment.
[0048] Combined with the newly provided sample data table (samples 21 to 30), we can analyze more comprehensively (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3 material performance change trend under different x values, SiO2 content (a value) and Fe2O3 content (b value). The following is a comprehensive analysis of these data: 1. The influence of x value 1. Change of x value: The x value increases from 0 (sample 24) to 0.55 (sample 29), covering the range from no A-site ion doping to higher doping levels.
[0049] 2. Density: As the x value increases, the density does not show an obvious linear relationship, which may be due to the complex influence of other components (SiO2 and Fe2O3) and possible phase or structural changes.
[0050] 3. Piezoelectric constant: The x value has a significant effect on the piezoelectric constant. In the lower and higher x value ranges (such as samples 21, 24, 25 and 29), the piezoelectric constant is low, and moderate x values (such as samples 23 and 26) generally show higher piezoelectric constants. This may be due to the increase in A-site ions improving the polarization response of the material, but too many A-site ions may lead to instability of the crystal structure.
[0051] 4. High temperature piezoelectric constant: Similar to the room temperature piezoelectric constant, the piezoelectric constant at high temperature also changes with the change of x value. A moderate x value is usually conducive to maintaining higher high temperature piezoelectric performance.
[0052] 5. Electromechanical coupling coefficient: The relationship between the electromechanical coupling coefficient and the x value is also relatively complex, but overall a moderate x value (such as around 0.3) helps to obtain a higher electromechanical coupling coefficient.
[0053] 6. Dielectric constant: The dielectric constant increases with the increase of x value, which may be due to the introduction of A-site ions that increase the polarization ability of the material. However, too high x value may cause the dielectric constant to grow slower or even decrease slightly (such as sample 29).
[0054] 2. Influence of SiO2 content (a value) 1. Changes in SiO2 content: The SiO2 content ranged from 0 (samples 22 and 27) to 0.25wt% (sample 26).
[0055] 2. Density: The addition of SiO2 usually increases the density of the material, but the effect is relatively small and complex (such as the comparison between sample 21 and sample 22).
[0056] 3. Piezoelectric constant: An appropriate amount of SiO2 (such as samples 23 and 26) helps to improve the piezoelectric constant. However, when the SiO2 content is too high or too low, the piezoelectric constant may decrease.
[0057] 4. High temperature piezoelectric constant: The effect of SiO2 on the high temperature piezoelectric constant is similar to that on the room temperature piezoelectric constant. An appropriate amount of SiO2 helps to maintain high high temperature piezoelectric properties.
[0058] 5. Electromechanical coupling coefficient: The effect of SiO2 content on the electromechanical coupling coefficient is not as significant as the piezoelectric constant, but the overall trend shows that an appropriate amount of SiO2 is conducive to obtaining a higher electromechanical coupling coefficient.
[0059] 6. Dielectric constant: The addition of SiO2 will significantly increase the dielectric constant, especially under high humidity conditions, however, excessive SiO2 (presumably) may lead to a slower increase in the dielectric constant.
[0060] 3. Influence of Fe2O3 content (b value) 1. Variation of Fe2O3 content: The Fe2O3 content ranged from 0 (samples 22 and 27) to 0.75wt% (sample 28).
[0061] 2. Density: Fe2O3 has a relatively small effect on density, but in some cases (such as the comparison between sample 22 and sample 23) it may lead to a decrease in density.
[0062] 3. Piezoelectric constant: The effect of Fe2O3 addition on the piezoelectric constant is more complicated. An appropriate amount of Fe2O3 (such as sample 23) may have a positive effect on the piezoelectric constant, but too much Fe2O3 (such as sample 28) will lead to a significant decrease in piezoelectric performance.
[0063] 4. High temperature piezoelectric constant: Similar to the room temperature piezoelectric constant, the piezoelectric constant at high temperature also changes with the change of Fe2O3 content. The right amount of Fe2O3 helps to maintain high high temperature piezoelectric properties.
[0064] 5. Electromechanical coupling coefficient: The electromechanical coupling coefficient is also affected by the Fe2O3 content, but the overall trend is not as obvious as the piezoelectric constant.
[0065] 6. Dielectric constant: The addition of Fe2O3 will increase the dielectric constant, but excessive Fe2O3 may cause the dielectric constant to grow slower or decrease slightly (such as the comparison between sample 28 and other samples).
[0066] Optimized combination of comprehensive analysis combining two sets of analyses: In order to obtain the best performance, the combination of x value, SiO2 content and Fe2O3 content needs to be considered comprehensively. For example, when the x value is moderate (such as 0.30-0.33), the SiO2 content is moderate (such as 0.05-0.1wt%), and the Fe2O3 content is moderate (such as 0.2-0.4wt%), the material may exhibit a higher piezoelectric constant, electromechanical coupling coefficient and dielectric constant.
[0067] Performance differences: Performance differences between different sample groups may be due to minor changes in the preparation process (such as temperature, time, mixing uniformity, etc.) and measurement errors, which have a smaller impact on this.
[0068] The analysis of the above samples shows that the chemical formula (Na2+Nb 2 / 5)xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3 material ratio and material selection, the obtained performance is jointly affected by the x value, SiO2 content (a value) and Fe2O3 content (b value), in order to obtain the desired performance, these parameters need to be carefully adjusted; at the same time, it is explained that the sensor element of the present invention can not only withstand higher operating voltages, but also maintain stable performance in high temperature and high humidity environments, and the product will not fail after long-term use, and is suitable for high temperature and harsh environments such as automotive engines, gas turbines, and boilers.
[0069] In summary, by precisely controlling the molar ratio and weight percentage of each component and optimizing the preparation process, it is ensured that the sensor element has excellent piezoelectric properties and can accurately convert mechanical vibrations into electrical signals. At the same time, the preparation method is detailed and the steps are clear. From raw material pretreatment to finished product testing, each step is strictly controlled and optimized to ensure the quality and consistency of the product.
[0070] The various devices selected in this application (components whose specific structures are not described) are all universal standard parts or components known to those skilled in the art, and their structures and principles can be known to those skilled in the art through technical manuals or conventional experimental methods.
[0071] In the description of the embodiments of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0072] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0073] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A high temperature piezoelectric sensor element, characterized in that: Its general chemical formula is: (Na2+Nb 2 / 5 )xTi(1-x)O3+aWt%SiO2+bWt%Fe2O3; in the formula (Na2+Nb 2 / 5 )xTi(1-x)O3 represents the basic ceramic powder material, aWt% represents the weight percentage of SiO2 in the ceramic powder, and bWt% represents the weight percentage of Fe2O3 in the ceramic powder; wherein (Na2+Nb 2 / 5 ) and Ti have a molar ratio of x:(1-x); a<0.1, b<0.5; and 0.25<x<0.35。 2. A method for preparing a high temperature piezoelectric sensor element as claimed in claim 1, characterized in that: include: S1, raw material pretreatment: put each chemical raw material into an oven at a constant temperature of 120℃~160℃ and dry it for 10~14h, then cool it to room temperature and take out the ingredients to be mixed; S2, ingredients; the dried sodium carbonate, titanium oxide, niobium pentoxide, silicon oxide, and iron oxide are mixed in a molar ratio of 36.55:44.9:18.3:0.05:0.2; S3, powder preparation: mixing the proportioned materials and crushing them to the required particle size; S4, preforming of the original part; adding the raw material powder into the mixed solvent, mixing, casting and punching into the required shape; S5, firing; removing the binder solid and a small amount of solvent components in the ceramic green sheet and sintering; S6, upper electrode; firing the ceramic sheet brushed with silver paste, and placing the fired ceramic sheet in a DC voltage to generate polarization intensity; S7, finished product testing; testing various parameters of the product.
3. The method for preparing a high temperature piezoelectric sensor element according to claim 2, characterized in that: The S3 further includes: S31, mixing; the mixed raw materials, ball milling medium and deionized water are fully stirred and mixed in a molar ratio of 1:2:0.6; S32, filter pressing; the mixed slurry is sealed and placed, and after standing, the air pressure valve is opened, and the pressure is 0.3-0.5MPa for filter pressing, and then closed after no water drips out; S33, drying; placing the filtered material in an oven at a constant temperature of 120°C to 160°C for drying to remove moisture from the surface of the material; S34, pre-firing; placing the material from which surface moisture has been removed into a pre-firing furnace and calcining it to form a porcelain material; wherein The heating rate of the pre-burning furnace is 4°C / min; and The maximum synthesis temperature was set at 1010°C to 1050°C and kept at this temperature for 2.5 h; S35, crushing: preliminarily crushing the pre-fired block porcelain material; S36, abrasive; the crushed porcelain material, ball milling medium and deionized water are fully stirred at a molar ratio of 1:2:0.6 to preliminarily grind the porcelain material, and then finely grind the preliminarily ground porcelain material to meet production requirements; S37, filter pressing; the ground porcelain powder slurry is sealed and placed, and after standing, the air pressure valve is opened, and the pressure is 0.3-0.5MPa for filter pressing, and then closed after no water drips out; S38, drying; placing the ceramic powder slurry after filter pressing into an oven at a constant temperature of 120°C to 160°C for drying, and obtaining ceramic powder after completely removing the moisture of the material.
4. The method for preparing a high temperature piezoelectric sensor element according to claim 3, characterized in that: The S4 further comprises: S41, slurry preparation; mixing ceramic powder, ball milling medium, adhesive and anhydrous ethanol in a molar ratio of 7.5:15:1.425:2.6 and rolling for 20 to 30 hours to prepare a uniform ceramic slurry with a certain viscosity; S42, tape casting; pouring the ceramic slurry into the tape casting box in the tape casting machine, the slurry on the moving steel belt is scraped by the tape casting scraper into a slurry layer of a certain thickness, and the formed ceramic film tape is taken out after being dried in the tape casting machine drying channel; wherein The conveying speed of the steel belt is 1 to 1.4 cm / s; and The drying oven temperature is 40°C to 60°C.
5. S43, isostatic pressing; the stacked ceramic membrane strip is statically pressed into shape using an isostatic pressing device; S44, punching: punching the isostatically pressed ceramic film strip into green sheets of the required shape.
6. The method for preparing a high temperature piezoelectric sensor element according to claim 4, characterized in that: The S5 further includes: S51, plastic removal; placing the green sheet into a plastic removal furnace for heating to remove the binder solid and a small amount of solvent components in the green sheet; wherein The heating rate of the plastic discharging furnace is 0.3°C / min; and The maximum temperature of the plastic discharging furnace is set to 600°C and kept warm for 0.5h; S52, sintering; placing the green sheet after plastic removal into an electric furnace and sintering for 1.2 hours; wherein The sintering temperature is 1200°C to 1260°C.
7. The method for preparing a high temperature piezoelectric sensor element according to claim 5, characterized in that: The S6 further includes: S61, silver coating: printing the silver paste onto the ceramic sheet through a screen printing device; S62, silver burning; placing the silver-coated ceramic sheet into a silver burning electric furnace so that the silver paste and the ceramic sheet are burned together to form an electrode; wherein The maximum temperature of the silver burning is 770°C and the temperature is kept for 0.2h; and The heating time for silver calcination is 1.8h. 8.S63, polarization; put the silver-sintered ceramic sheet into a polarization box in an oven, set the temperature to 100°C, and use a withstand voltage tester to slowly pressurize to 6-7KV to generate polarization strength for the ceramic sheet.
9. The method for preparing a high temperature piezoelectric sensor element according to claim 6, characterized in that: The S7 includes: S71, appearance inspection; inspect product appearance and remove defective products.
Citation Information
Patent Citations
A low-temperature sintered piezoelectric ceramic material and its preparation method
CN109320244B
Low temperature sintering piezoelectric ceramic material and preparation method thereof
CN102850050A
Piezoelectric ceramic composite for application tomultilayer actuator and manufacturing method thereof
KR1020040046472A
